Islamic Mysticism and Persian Literature: The Case of Rumi’s Mathnawi - Mirbagheri Fard, Ali Ashgar (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
Islamic Mysticism and Persian Literature: The Case of Rumi’s Mathnawi